OPTIMIZING THE ROLE OF NORTH SUMATERA BAWASLU IN COMBATING MONEY POLITICS: A LEGAL AND EMPIRICAL ANALYSIS - Haura Nurfadilla Lubis; Rizkan Zulyadi; Mirza Nasution (JUPIIS: JURNAL PENDIDIKAN ILMU-ILMU SOSIAL, 2026)
This study analyzes the optimization of the function of the General Election Supervisory Agency (Bawaslu) in law enforcement of money politics crimes in the election, with a case study at the North Sumatra Provincial Bawaslu Office. Money politics is an election criminal offense that threatens the legitimacy of election results and the quality of democracy. This research uses normative juridical approaches and empirical juridical approaches through in-depth interviews and document studies. The results of the study show that the form of law enforcement carried out by Bawaslu includes administrative, criminal, and code of ethics aspects. Steps to resolve money politics cases are carried out through the mechanism of the Integrated Law Enforcement Center (Gakkumdu) involving Bawaslu, the Police, and the Prosecutor's Office with strict time limits. However, optimizing the role of Bawaslu still faces legal obstacles (differences in election and regional election regulations, short deadlines) and non-legal obstacles (limited human resources, budget, cross-agency coordination, and low community legal culture). This study concludes that it is necessary to harmonize regulations, increase institutional capacity, strengthen coordination, and community participation so that law enforcement of money political crimes can run effectively and realize elections with integrity. Keywords: Bawaslu, Money Politics, Law Enforcement